Analisis Video Animasi Nusa dan Rara dalam Menanamkan Nilai Tanggung Jawab pada Anak Usia 5-6 - Ismi Ulfatul Ilmiyah; Mailinda Anis Zulaiha (AS-SABIQUN, 2026)
Although the development of children aged 5–6 years is very significant, responsibility remains a relatively weak aspect and requires strengthening through appropriate learning strategies. This study aims to assess the contribution of the Nusa dan Rara animated videos in instilling a sense of responsibility in children aged 5–6 years. This study employed a descriptive qualitative approach involving 15 children at SPS Lemuru 88. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing to obtain a deeper understanding of children’s behavior. The results showed that the use of the Nusa dan Rara animated videos had a positive impact on improving the value of responsibility in children. The children showed fairly significant behavioral changes, such as obeying rules during activities, becoming more independent, maintaining environmental cleanliness, putting toys away after use, and having the courage to admit mistakes. These changes indicate that children are able to recognize and imitate the positive behaviors displayed in the animated videos. These findings are in line with Bandura’s social learning theory, which emphasizes that children acquire knowledge through the processes of observing, imitating, and receiving reinforcement. This study concludes that the use of animated videos is an effective way to instill the value of responsibility in early childhood, especially when supported by teacher guidance and conducive learning conditions. The implications of this study underscore the importance of utilizing audio-visual media in learning to strengthen character education while opening opportunities for further research on the use of new media in instilling moral values in children.